Expanding the frontiers of visual analytics and visualization - Dill, John. (Springer London, 2012)
The data deluge problem is increasing. Every day the results of scientific experiments, monitoring instruments, medical analysis, and social networks add petabytes to the world’s information. Many future experiments will generate data that will be substantially more than has been collected throughout history. How can we effectively translate this into meaningful information, particularly if there is a time critical element to the data? Although Moore’s law results in an ever-decreasing cost of processing, storage, and transmission – so that the data can be stored and transmitted – it does not necessarily follow that the data can be processed effectively. Visual analytics seeks to facilitate analytical reasoning supported by interactive visual interfaces in order to integrate the human into the analysis process. Expanding the Frontiers of Visual Analytics and Visualization contains international contributions by leading researchers from within the field. Dedicated to the memory of Jim Thomas, the book begins with the dynamics of evolving a vision based on some of the principles that Jim and colleagues established and in which Jim’s leadership was evident. This is followed by chapters in the areas of visual analytics, visualization, interaction, modelling, architecture, and virtual reality, before concluding with the key area of technology transfer to industry. Visual analytics and visualization bring together the areas of computer science, information visualization, cognitive and perceptual sciences, interactive design, graphic design, and social sciences. List of contributors -- Introduction – the best is yet to come -- Part 1: evolving a vision -- An illuminated path: the impact of the work of Jim Thomas -- The evolving leadership path of visual analytics -- Part 2: visual analytics and visualization -- Visual search and analysis in complex information spaces – Approaches and research challenges -- Dynamic visual analytics – Facing the real-time challenge -- A review of uncertainty in data visualization -- How to draw a graph, revisited -- Using extruded volumes to visualize time-series data sets -- Event structuring as a general approach to building knowledge in time-based collections -- A visual analytics approach for protein disorder prevention -- Visual storytelling in education applied to spatio-temporal multivariate statistics data -- Part 3: interaction and user interfaces -- Top ten interaction challenges in extreme-scale visual analytics -- GUI 4D – the role and the impact of visual, multimedia and multilingual user interfaces in ICT applications and services for users coming from the bottom of the pyramid – First concepts, prototypes, and experiences -- Emotion in human computer interaction -- Applying artistic color theories to visualization -- E-culture and M-culture: the way that communication systems and mobile devices are changing the nature of art, design and culture -- Part 4: modeling and geometry -- Shape identification in temporal data sets -- SSD-C: smooth signed distance colored surface reconstruction -- Geometric issues in object manipulation in task animation and virtual reality -- An analytical approach to dynamic skin deformation for character animation -- Part 5: architecture and displays -- The new visualization engine – the heterogeneous processor unit -- Smart cloud computing -- Visualization surfaces -- Part 6: virtual reality and augmented reality -- The development of mobile augmented reality -- Multimodal interfaces for augmented reality -- Part 7: technology transfer -- knowledge exchange, technology transfer and the academy -- Discovering and transitioning technology -- Technology transfer at IBBT-EDM: a case study in the computer graphics domain -- Building adoption of visual analytics software -- Author index.